2022
DOI: 10.3389/or.2022.10570
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Studies on the Seasonal Variation of Indoor Radon-222 Concentration

Abstract: Due to their electrostatic nature, radon decay products can attach to solid particles and aerosols in the air. Inhalation and ingestion are therefore the two main routes through which people are exposed to radon and its decay products. During the inhalation of these radioactive aerosols, deposition takes place in different regions of the human respiratory tract. The deposited aerosols carrying radon and its progeny undergo a continuous radioactive transformation and expose the lung to ionizing alpha radiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…Although other studies report an association between seasonality and indoor radon concentrations [32,[50][51][52][53][54], time of year did not predict indoor radon values in our study. Brookins [32] found that radon concentrations in homes in the Albuquerque, New Mexico area with refrigerated air conditioning did not show the same seasonal radon variability (high in winter and low in summer) as did homes without refrigerated air conditioning (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Although other studies report an association between seasonality and indoor radon concentrations [32,[50][51][52][53][54], time of year did not predict indoor radon values in our study. Brookins [32] found that radon concentrations in homes in the Albuquerque, New Mexico area with refrigerated air conditioning did not show the same seasonal radon variability (high in winter and low in summer) as did homes without refrigerated air conditioning (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…They observed a maximum radon concentration of 1481 Bq m –3 in a house with a basement and a maximum of 210 Bq m –3 without a basement. [ 27 ] Because Laboratory‐1 is located in the basement of an old building and the radon rises along with the soil and is compressed under the building, it escapes through the cracks and spaces in the walls of the laboratory, causing higher radon activity concentrations compared to the other stations. In addition, the closure of schools and the lack of use of stations due to the pandemic (COVID‐19) has caused an increase of indoor radon activity concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have been conducted on the seasonal variability of indoor radon concentration levels [ 7 , 8 , 11 , 13 15 ]. Studies conducted globally to determine indoor radon concentration during winter (rainy season) and summer (dry season) [ 8 , 11 , 13 , 15 17 ] weather seasons aim to find out which seasonal period contains higher indoor radon levels. The studies conducted in Ghana and abroad reported higher indoor radon levels during the rainy (winter) season which were mainly linked to the windows and doors normally closed due to the rains and little bit colder compared to the dry (summer) season, resulting in an accumulation of radon in the room coming from the soil underneath the building and construction materials [ 7 , 8 , 11 , 17 , 13 ].…”
Section: Introductionmentioning
confidence: 99%